Research on the theoretical significance and practical value of Tai Chi incorporating into community care services - Cao, Zurui; Yang, Hongjun (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: In recent years, in order to alleviate the social aging situation, my country has vigorously developed community elderly care services, continuously improved the home care environment, and met the needs of the elderly for social services, thus forming a new type of social elderly care service system based on family and community elderly care services. However, there are still many problems in advancing the construction of community elderly care services, such as insufficient medical care and fitness facilities, lack of spiritual culture and recreational activities, and standardization of elderly care services. In order to solve the status quo of community elderly care, it is necessary to enrich the community elderly care service model. Tai Chi exercise is very helpful to the elderly in terms of health care, spiritual entertainment, etc. Tai Chi exercise is also a fitness and entertainment activity that many elderly people like. This study systematically analyzes the theoretical significance and practical value of Tai Chi into community elderly care services, and provides a reference for Tai Chi to integrate into community elderly care services. Method: Literature data method. This study adopts the literature data research method, using CNKI, Baidu Academic, VIP and other websites to search and collect literature data related to Tai Chi exercise and community elderly care services for the theoretical basis of this research; interview method, right Analyze the theoretical significance and practical value of Tai Chi movement into community elderly care services; logical analysis method, in the research process of this article, use logical analysis methods such as induction, deduction, comparison, and synthesis to extract, analyze, and process relevant information. Results: (1) Fitness effect. The fitness value of Tai Chi exercise is extremely significant in the rehabilitation effect of fitness therapy, especially for the elderly. Tai Chi exercise has a significant rehabilitation effect on the diseases of the elderly such as rheumatism, frozen shoulder and hyperosteogeny. It has a good effect on neurasthenia and hypertension in the elderly. Through Tai Chi exercise, the joints and tissues of the elderly are improved, and the body functions are significantly enhanced. Long-term adherence to Tai Chi exercise can promote blood flow and enhance the pumping function of the heart. This shows that Health Tai Chi exercise is also very helpful in improving the cardiovascular system. In addition, Tai Chi exercise can also enhance the sensitivity of the nervous system and can effectively slow down the deterioration of the elderly motor function. Therefore, Tai Chi exercise plays an important role in health care, anti-aging, and longevity of the elderly. (2) Fitness methods. Tai Chi is pure aerobic exercise. It is a moderate exercise that is strong but not vigorous. It is performed in a gentle and slow state. There is no safety hazard for the elderly during exercise. The movements are simple, easy to master, there is no difficulty in learning, and the enthusiasm is high. More importantly, Tai Chi exercises are of low intensity and are suitable for people of different groups, different physiques, and different ages, especially the elderly. (3) Pleasure physically and mentally. Regularly carry out Tai Chi movement performance activities in the community to enrich the spiritual life of the elderly and deepen the elderly understanding of healthy elderly care. In the Tai Chi movement learning stage, the elderly concentrate on learning and imitating movements, subtly improving the elderly ability to observe things and attention, and enhance the elderly thinking ability. In addition, it also improves the happiness and entertainment of the elderly, promotes the enthusiasm of the elderly to participate in fitness activities, reduces the anxiety, depression and loneliness of the elderly, promotes the mental health of the elderly, and improves the social interaction of the elderly ability. (4) The venue. Tai Chi exercise is less constrained by the venue, and the elderly can exercise on flat ground. If the weather is good, they can exercise outdoors, while exercising, they can breathe fresh air and feel the charm of nature, which is more conducive to the health of the elderly. If the weather is bad, they can choose to exercise indoors without interrupting the elderly exercise program. (5) In terms of funding. In an aging society, my country’s social security system is not mature enough and the level of social consumption is not high. In order to reduce the medical expenditures of the elderly, promote the harmonious development of the society, and improve the quality and level of life of the elderly, my country has specifically proposed a national fitness programs to reduce the incidence of diseases in the elderly. Tai Chi exercise is an important help to the health of the elderly and the rehabilitation of some diseases. It is basically non-consumable economically, and can ease the pressure of financial investment in community elderly care services and reduce the economic burden on families and communities. Conclusion: Tai Chi has an important position and function in our country's community elderly care services. Tai Chi movements are simple and easy to master. The elderly has no safety hazards during exercise; it has a significant effect on the improvement of the physical, psychological and functional conditions of the elderly; enriches the spiritual life of the elderly, improves happiness and entertainment, and promotes psychology Health; it can alleviate the pressure of financial investment in community elderly care services, reduce the economic burden of families and communities, and promote the harmonious development of society. Therefore, Tai Chi exercise should be integrated into community elderly care services, so as to promote the construction of community elderly care services and improve the health quality and living standards of the elderly.